Building standardized scores for the physical tests used in the admission of students applying for the Faculty of Physical Education and Sports Sciences at the University of Benghazi - Fathi Al-Warshafani; Al-Fazzani, Mohammed; Al-Haddad, Tawfiq (Journal of Pure & Applied Sciences, 2021)
The study aims to establish standard scores for the physical fitness tests used in the admission process of new students at the Faculty of Physical Education and Sports Sciences at the University, and the researcher used the descriptive method in his survey style, and the study sample was chosen by the intentional method from the community of new students applying for admission tests to study at the Faculty of Physical Education, University of Benghazi For the academic year 2018-2019, and the size of the study population reached (80) students, and physical tests were used as tests to accept new students, and the number of tests used was (6) tests, and a standardized score was reached for each test of physical fitness. The most important recommendations refer to the necessity of using the T-criteria for physical fitness tests in the selection programs for new students to study at the College of Physical Education and Sports Sciences, due to the specificity of these criteria in the local community, and it is also recommended to re-use the tests in consecutive studies to see the extent of the development of physical fitness among students And it recommends that attention should be paid to conducting more studies aimed at setting standard levels in aspects a For another, to be a selection function for students applying to study at the Faculty of Physical Education and Sports Sciences at the University of Benghazi.